2003
DOI: 10.1111/j.1525-1470.2003.20616.x
|View full text |Cite
|
Sign up to set email alerts
|

Harlequin Baby with Ecthyma Gangrenosum

Abstract: Pseudomonas aeruginosa bacteremia or sepsis often occurs in hospitals, affecting mainly children with underlying disease. Ecthyma gangrenosum is classically considered a pathognomonic sign of sepsis by P. aeruginosa. The harlequin baby, a severe variant of ichthyosis, occurs rarely, and these infants are at high risk of cutaneous infections and sepsis. We herein report a harlequin baby who developed ecthyma gangrenosum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…A weak mechanical defense barrier and underdeveloped cellular or humoral immunity increased the risk of infection in newborns [ 4 , 5 ]. In the general population lesions are usually present in the gluteal and perineal regions or on the extremities and trunk, but rarely are they found on the face or neck [ 6 ], whereas, in most reported cases of preterm EG, the face is affected as was the case in our patient [ 7 , 8 ]. Even though literature has shown that most children with EG had either previously undetected immunodeficiencies or transient risk factors such as immunosuppressive therapy that predisposed them to the development of the disease, not many newborn cases have been reported [ 9 ].…”
Section: Discussionmentioning
confidence: 72%
“…A weak mechanical defense barrier and underdeveloped cellular or humoral immunity increased the risk of infection in newborns [ 4 , 5 ]. In the general population lesions are usually present in the gluteal and perineal regions or on the extremities and trunk, but rarely are they found on the face or neck [ 6 ], whereas, in most reported cases of preterm EG, the face is affected as was the case in our patient [ 7 , 8 ]. Even though literature has shown that most children with EG had either previously undetected immunodeficiencies or transient risk factors such as immunosuppressive therapy that predisposed them to the development of the disease, not many newborn cases have been reported [ 9 ].…”
Section: Discussionmentioning
confidence: 72%
“…6 Another newborn infant with EG was a harlequin baby and the agent was P. aeruginosa. 16 However, Candida albicans was detected in a 12 day old newborn infant with EG. 17 The predominance of prematurity among newborn cases with EG make us think about immunodeficiency of preterm infants.…”
Section: Discussionmentioning
confidence: 96%
“…For the first month of life, until the deep fissures heal, sepsis remains a threat and is unfortunately the leading cause of death in these patients [2]. Despite the risk of sepsis, quite interestingly there are no data available which supports antibiotic therapy in these patients and in a case reported by Gunes et al, the patient died on day 21 after being administered antibiotic treatment [9].…”
Section: Discussionmentioning
confidence: 99%